Paleomagnetism of the komatiitic basalts of the Ottawa Islands, N.W.T. - Buchan, K. L.; Baragar, W. R. A. (Canadian Journal of Earth Sciences, 1985)
The komatiitic basalts of the Ottawa Islands in eastern Hudson Bay are on strike with and believed to form a continuation of similar units of the Cape Smith Belt 150 km to the northeast. Units sampled in the Ottawa Islands all dip gently to the west and hence are not suitable for an internal fold test of their age of magnetization. However, before correcting for the tilt of the lavas, the dominant magnetization direction (D = 207.6°, I = 61.9°, k = 168, α 95 = 3.7°) does not differ significantly from the uncorrected magnetization direction reported from the steeply dipping, northwest-facing units at Cape Smith (D = 218°, I = 60°, k = 47, α 95 = 4°). This negative fold test suggests that the remanence at both locations was acquired after folding. Comparison with the North American Precambrian apparent polar wander path implies that overprinting is related to the Hudsonian Orogeny.A second stable magnetization directed to the west with a shallow inclination is superimposed on the dominant component at a number of sampling sites. Its direction is poorly defined and no fold test is possible. However, magnetic evidence suggests that this component was probably acquired as an overprint after the dominant magnetization, perhaps during a mild reheating associated with the Elsonian Orogeny.